PENILAIAN KESEHATAN KEUANGAN PADA KOSPIN JASA SYARIAH PEKALONGAN SEBAGAI LEMBAGA KEUANGAN MIKRO SYARIAH - Rinda Astuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2011)
Supervision of Islamic microfinance institutions (LKMS) is necessary to control financing activities and to assess whether these financial institutions are operating in a healthy condition. Financial assessments are conducted by authorized agencies through audits of the financial system using the services of independent auditors, as stipulated in the Regulation of the Minister of Cooperatives and Small–Medium Enterprises No. 14/Per/M.KUKM/XII/2009. Although provisions regarding health assessment audits have been regulated, LKMS—such as KJSP—are allegedly not yet equipped with standard operating procedures to achieve the standards set out in the ministerial regulation. In the absence of such standards, this study aimed to assess the financial health of KJSP. This research employed a quantitative approach, relying on primary data obtained from KJSP’s financial reports during 2004–2009 and interviews with KJSP managers. The results show that KJSP’s assets reached 66.503 billion in 2009 and were categorized as “Healthy,” as most calculated financial ratios met the required standards, while the capital ratio was categorized as “Fairly Healthy.” However, the study encountered organizational constraints that limited the scope of the assessment. The main constraint was related to KJSP’s position as a small unit within the larger entity, Kospin JASA, which still operates using conventional financial services.